2003
DOI: 10.1303/aez.2003.583
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bombyxin-II, an insulin-related peptide of insects, on Bombyx mori hemocyte division in single-cell culture

Abstract: We examined the effect of an insulin-related peptide, bombyxin-II, on the mitotic division of Bombyx mori hemocytes in vitro. Hemocytes isolated from larval hemolymph (day 1 of 4th instar) were cultured singly in MGM-450 medium. Some cultured prohemocytes (11.1%), plasmatocytes (2.6%), granulocytes (8.5%) and spherulocytes (10.8%) underwent mitotic division in the medium. Synthetic bombyxin-II added to the medium together with 10% larval hemolymph notably increased the ratio of dividing granulocytes to 45.5%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
0
10
1
Order By: Relevance
“…Bombyxin has attracted considerable attention from physiologists due to its apparently diverse range of target tissues. It has been described as an ecdysiotropin [23], a regulator of growth [29,30], metamorphosis [14], hematopoiesis [26,35], sugar metabolism [36,37,18] and of ovarian development [5]. The diversity of reported targets of ILPs encourages the expectation that bombyxin and related ILPs may also be important hormonal messengers of time.…”
Section: Introductionmentioning
confidence: 99%
“…Bombyxin has attracted considerable attention from physiologists due to its apparently diverse range of target tissues. It has been described as an ecdysiotropin [23], a regulator of growth [29,30], metamorphosis [14], hematopoiesis [26,35], sugar metabolism [36,37,18] and of ovarian development [5]. The diversity of reported targets of ILPs encourages the expectation that bombyxin and related ILPs may also be important hormonal messengers of time.…”
Section: Introductionmentioning
confidence: 99%
“…For insects on the contrary, reports on the involvement of ILPs in carbohydrate metabolism are rare (Satake et al, 1997;Rulifson et al, 2002;Broughton et al, 2005). Most research has focused on the role of ILPs in controlling cell, organ and total body size and growth (Chen et al, 1996;Brogiolo et al, 2001;Ikeya et al, 2002;Nijhout and Grunert, 2002;Malaterre et al, 2003;Nijhout, 2003;Saito and Iwabuchi, 2003;Stern, 2003;Goto et al, 2005;LaFever and Drummond-Barbosa, 2005). Additionally, ILPs appear to be involved in controlling life-span (Clancy et al, 2001;Tatar et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Many authors (Gardiner and Strand, 2000;Tu et al, 2002;Saito and Iwabuchi, 2003;Okazaki et al, 2006) reported that the maintenance of hemocyte populations is thought to be regulated by the mitotic division of circulating hemocytes and by production and release of hemocytes in the hematopoietic organs. Mitotic index (MI) is a measure for the proliferation status of a hemocyte population and can be defined as "the ratio between the number of cells, in a population undergoing mitosis, to THC in a population".…”
Section: Mitotic Index As a Parameter Of Haemogram Profile In Insectsmentioning
confidence: 99%